Surveillance for feline herpesvirus type 1 mutation and development of resistance in cats treated with antiviral medications - Lewin, Andrew C.; Ineck, Nikole E.; Mironovich, Melanie A.; Marino, Morgan E.; Liu, Chin-Chi; Emelogu, Ugochi; Mills, Erinn P.; Camacho-Luna, Pilar; Carter, Renee T. (Frontiers in Veterinary Science, 2023)
Feline herpesvirus type 1 (FHV-1) commonly causes ocular surface disease in cats and is treated with antiviral medications targeting viral DNA polymerase (UL30/42). Herein, we describe a method to assess the FHV-1 genome for mutation development and to assess the functional impact of mutations, if present. Fourteen shelter-housed domestic cats with FHV-1 ocular surface disease were assigned to one of four treatment groups: placebo (n=3), cidofovir 0.5% ophthalmic solution (n=3), famciclovir oral solution (n=5), or ganciclovir 0.15% ophthalmic solution (n=3). Swabs were collected before (day 1) and after (day 8) one week of twice-daily treatments to isolate viable FHV-1. Viral DNA was extracted for sequencing using Illumina MiSeq with subsequent genomic variant detection between paired day 1 and day 8 isolates. Plaque reduction assay was performed on paired isolates demonstrating non-synonymous variants. A total of 171 synonymous and 3 non-synonymous variants were identified in day 8 isolates. No variants were detected in viral UL23, UL30, or UL42 genes. Variant totals were not statistically different in animals receiving antiviral or placebo (p=0.4997). A day 8 isolate from each antiviral treatment group contained a single non-synonymous variant in ICP4 (transcriptional regulator). These 3 isolates demonstrated no evidence of functional antiviral resistance when IC50 was assessed. Most (10/14 pairs) day 1 and 8 viral isolate pairs from the same host animal were near-identical. While functional variants were not detected in this small sample, these techniques can be replicated to assess FHV-1 isolates suspected of having developed resistance to antiviral medications.